A model for solving the problem of Neonatal death in the unrest situation of Narathiwat Province, 2021-2022 - Hayeemayeng, Royan; Musoor, Yameilah; Sirikun, Phensiri; Hayeese, Wanisa (Princess of Naradhiwas University Journal, 2023)
This research aimed to develop and assess the suitability of a model for solving the problem of neonatal death in the unrest situation in Narathiwat Province in 2021–2022. There are two sections to the integrated model. 1) qualitative research was divided into three steps: the study of problem situations, analysis of the composition, and development of a model for solving neonatal death 2) quantitative research to assess the appropriateness of the problem-solving model. The tool used was a questionnaire developed by the researcher, which passed the content compliance check (IOC) with a value between 0.67-1.00. The study’s findings revealed that the problem-solving model for neonatal death in Narathiwat Province’s unrest situation was divided into two parts: part 1 was composed of seven aspects of management, and part 2 was composed of four factors supporting its implementation. Problem-solving model is very appropriate, mean 4.14 ± 0.458. When classifying the side of the average by the side, it was found that in Part 1, Staffing had the highest average value of 4.19 ±0.547, followed by Planning at 4.18 ± 0.568, Reporting 4.17 ± 0.558, Co-ordinating 4.15 ± 0.571, Organizing 4.14 ± 0.549, Directing 4.09 ± 0.630, and Budgeting 4.00 ± 0.584, respectively. Part 2 Factors supporting the implementation, The highest average was Service System 4.24 ± 0.529, followed by Information system 4.15 ± 0.585, Teams work 4.11 ± 0.569, and Participation 4.06 ± 0.583 respectively.